WASTE-PAPER CRAFTS AT GEGAEN LIMA CRAFT, SUDAJI VILLAGE, SAWAN DISTRICT, BULELENG REGENCY - Muh Efendi; Luh Suartini; I Wayan Sudiarta (Universitas Pendidikan Ganesha, 2026)
This study aims to determine: (1) The tools and materials used in the production of waste-paper crafts at Gegaen Lima Craft, Sudaji Village, Sawan Subdistrict, Buleleng Regency. (2) The process of producing waste-paper crafts at Gegaen Lima Craft, Sudaji Village, Sawan Subdistrict, Buleleng Regency. (3) To identify the types of waste-paper crafts at Gegaen Lima Craft, Sudaji Village, Sawan Subdistrict, Buleleng Regency. The research design employed is qualitative descriptive research. The object of this study is waste-paper crafts at Gegaen Lima Craft, Sudaji Village, Sawan Subdistrict, Buleleng Regency. Data collection methods included observation, interviews, documentation, and literature review. The research results indicate that: (1) the tools and materials used include scissors, a cutter, a ruler, a brush, bamboo, a wood-handled awl, and a turntable. The materials used to create waste-paper crafts include used paper, white glue, and water-based wood stain. (2) The first stage of the paper waste craft production process involves preparing the used paper through to the finishing process. (3) The types of waste-paper crafts produced include lidded candy boxes, fruit baskets, flower vases, bokor, coasters, key chains, dulang, rugs, saab, and bags.